Determinants of job turnover intentions: Evidence from Singapore - XING, Xiaolin (Institutional Knowledge at Singapore Management University, 2005)
This paper explores both observable and unobservable variables that would affect employed workers’ decisions on job change. We find that age, job satisfaction, satisfaction with working environment or job security, and firm size are among the major factors determining workers’ intentions of job-to-job mobility. Younger workers and workers in smaller firms are more likely to look for other jobs. We also find that men are more likely to consider a change in job than women, but when “actually looking for another job” is concerned, men and women do not differ. Furthermore, monthly income and working sector contribute significantly to looking for other jobs.